PEMBERDAYAAN PETERNAK SAPI MELALUI PENERAPAN TEKNOLOGI TEPAT GUNA MESIN PENCACAH RUMPUT UNTUK MENINGKATKAN EFISIENSI PAKAN DAN PRODUKTIVITAS USAHA - Hikmah Adwin Adam; Bister Purba; Pina Budiarti Pratiwi; Raina Rosanti; Desri Wiana (Jurnal Ilmiah Madiya (Masyarakat Mandiri Berkarya), 2026)
Small-scale cattle farming plays an important role in supporting rural livelihoods; however, inefficient forage utilization remains a major constraint on production costs and farm productivity. This problem was identified among cattle farmers in Sumber Karya Village, Binjai City, where elephant grass was provided without prior chopping, resulting in substantial forage waste and increased feeding costs. This community service program aims to improve feed efficiency and livestock productivity by implementing an appropriate technology, a forage chopping machine. The program adopted a Participatory Rural Appraisal (PRA) approach, which included needs assessment, machine design and fabrication, operational training, mentoring, monitoring, and evaluation. The forage chopper was designed with a capacity of 200 kg per hour and produced chopped forage measuring 2–5 cm, making it easier for cattle to consume. The results demonstrated that the technology reduced forage waste, which had previously reached approximately 25–30%, improved feed utilization efficiency, and lowered daily feed costs by approximately IDR 30,000. Furthermore, the training enhanced the partner's capability to operate and maintain the machine independently, ensuring the sustainability of the technology adoption. Overall, the program demonstrates that the application of appropriate technology can effectively improve feed efficiency, increase livestock productivity, and strengthen the economic sustainability of small-scale cattle farming.